2019
DOI: 10.1002/gj.3611
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology and geochemistry of late Carboniferous–Middle Jurassic magmatism in the Helong area, NE China: Implications for the tectonic transition from the Paleo‐Asian oceanic to circum‐Pacific regime

Abstract: In this study, we present new U–Pb zircon ages and whole‐rock major and trace element data for the late Carboniferous–Middle Jurassic intrusive rocks in the Helong area, NE China. These data constrain the timing of tectonic transition from the Paleo‐Asian oceanic regime to the circum‐Pacific regime. U–Pb zircon dating indicates that the late Carboniferous–Middle Jurassic magmatic events in the Helong area can be subdivided into late Carboniferous, middle Permian, Early–Middle Triassic, Late Triassic, Early Jur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 76 publications
(178 reference statements)
1
17
0
Order By: Relevance
“…However, these igneous rocks are classified as late Paleozoic based on K-Ar ages and lithostratigraphic relationships [36]. Thus, previous studies have shown that the voluminous igneous rocks include Late Permian-Cretaceous rocks [5,16,34,37,38]. Furthermore, according to their emplacement ages, the Late Permian-Triassic igneous rocks in study area could be divided into the three groups: (1) Late Permian, (2) Early Triassic, and (3) Middle Triassic [5,16,30,34,37].…”
Section: Geological Background and Sample Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these igneous rocks are classified as late Paleozoic based on K-Ar ages and lithostratigraphic relationships [36]. Thus, previous studies have shown that the voluminous igneous rocks include Late Permian-Cretaceous rocks [5,16,34,37,38]. Furthermore, according to their emplacement ages, the Late Permian-Triassic igneous rocks in study area could be divided into the three groups: (1) Late Permian, (2) Early Triassic, and (3) Middle Triassic [5,16,30,34,37].…”
Section: Geological Background and Sample Descriptionsmentioning
confidence: 99%
“…Thus, previous studies have shown that the voluminous igneous rocks include Late Permian-Cretaceous rocks [5,16,34,37,38]. Furthermore, according to their emplacement ages, the Late Permian-Triassic igneous rocks in study area could be divided into the three groups: (1) Late Permian, (2) Early Triassic, and (3) Middle Triassic [5,16,30,34,37]. However, the poor exposure of The study area is to the east of Helong City, in the southern Yanbian area ( Figure 2B) and is located at the eastern segment of the CAOB.…”
Section: Geological Background and Sample Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study undertaken by Tang, Li and Xu (, this issue), the authors present new U–Pb zircon ages and whole‐rock major and trace element data for the late Carboniferous–Middle Jurassic intrusive rocks in the Helong area, NE China. These data put a robust constraint of the timing of tectonic transition from the Paleo‐Asian oceanic regime to the circum‐Pacific regime on the Late Triassic‐Early Jurassic.…”
Section: Eastern Altaidsmentioning
confidence: 99%
“…The mechanism by which PMMs develop in peridotites reveals that some podiform chromite in this area may also be xenoliths that formed after chromite was captured by ultramafic magmas in early times. In the study undertaken by Tang, Li and Xu (2020, this…”
Section: Western Altaidsmentioning
confidence: 99%